effect of dietary citrus pectin on the excretion of human fecal neutral and acid steroids and the activity of 7alpha-dehydroxylase and beta-glucuronidase - Ross, J.K; Leklem, J.E (The American journal of clinical nutrition, 1981)
The purpose of this study was to investigate the effects of citrus pectin on human fecal neutral and acid steroid excretion and beta-glucuronidase and 7alpha-dehydroxylase activity. Eight healthy male subjects (age 20 to 27 yr) were used in a switchback design with or without 15 g citrus pectin added to a mixed low fiber diet. There were three successive 18-day periods preceded by a 4-day adjustment period. Half of the subjects followed a pectin-nonpectin-pectin protocol and the other half followed a nonpectin-pectin-nonpectin protocol. Fecal samples were collected throughout the study under anaerobic conditions. Compared to the control diet, mean fecal weight, percentage moisture, transit time, and fecal fat for both groups of subjects were not significantly different by analysis of variance when subjects were fed pectin diet. Mean beta-glucuronidase activity was increased (35%) when subjects were fed the pectin. Mean 7alpha-dehydroxylase activity showed no definite trend. Mean neutral steroid concentration was slightly decreased (8%) when the pectin diet was fed but total excretion was unchanged. End of period neutral steroid concentration was decreased 9% and total excretion was decreased 3.5%. Mean acid steroid concentration was not changed but total excretion was increased (11%) on the pectin diet. End of period acid steroid concentration and excretion was increased 6% on the pectin diet. This study shows that there were interrelationships between dietary pectin, neutral and acid steroid metabolism, and bacterial enzyme activity.